IMPLICATIONS OF THREATS IN THE NORTH NATUNA SEA FOLLOWING THE JOINT STATEMENT BETWEEN THE REPUBLIC OF INDONESIA AND THE PEOPLE'S REPUBLIC OF CHINA - Pratondo Ario Seno Sudiro (Budi Luhur Journal of Strategic & Global Studies, 2025)
Abstract: North Natuna Sea is part of South China Sea which is included in the territory of the Republic of Indonesia. The highlight of the region is People Republic of China’s claim known as Nine Dash Line and also The U-shaped Line. Based on their claim, Chinese government sent the China Coast Guard Patrol Vessel to patrol along The Nine Dash Line. Consequently, the patrol vessel one appeared inside the Exclusive Economic Zone of Indonesia in North Natuna Sea. The latest development is the signing of the Joint Statement between both countries at 9th November, 2024 include joint development in areas of overlapping claims, which triggered pros and cons reactions among the experts. Based on those, this literature research aims to analyze implication to the threat in North Natuna Sea post the signing of Joint Statement. This research results is statement that Joint Statement between both countries can defuse the threat in North Natuna Sea, so that it should be followed by the other countries in South China Sea area.   Abstrak: Laut Natuna Utara merupakan bagian dari wilayah Laut China Selatan yang termasuk ke dalam wilayah kedaulatan Negara Kesatuan Republik Indonesua. Hal yang menonjol dari wilayah ini adalah adanya klaim Republik Rakyat China (RRC) yang dikenal dengan Nine Dash Line dan juga The U-shaped Line. Berdasarkan klaimnya, pemerintah RRC mengirimkan Kapal Patroli China Coast Guard untuk berpatroli di sepanjang Nine Dash Line yang mengakibatkan kehadiran mereka dalam wilayah ZEE NKRI di Laut Natuna Utara. Perkembangan terkini adalah ditandatanganinya Joint Statement antara kedua negara pada 9 November 2024 termasuk ‘joint development in areas of overlapping claims’ yang telah memicu reaksi pro dan kontra di kalangan para ahli. Berdasarkan hal itu, studi literatur ini bertujuan menganalisis implikasi terhadap ancaman di Laut Natuna Utara pasca-Joint Statement. Hasil penelitian ini adalah statement bahwa Joint Statement antara kedua negara dapat meredakan ancaman di Laut Natuna Utara, yang seharusnya diikuti oleh negara-negara di kawasan Laut China Selatan lainnya.